2018
DOI: 10.1038/s41598-018-34931-5
|View full text |Cite
|
Sign up to set email alerts
|

Water drainage from Kushiro Coal Mine decreased on the day of all M ≥ 7.5 earthquakes and increased thereafter

Abstract: The amount of water drainage from Kushiro Coal Mine in Hokkaido, Japan decreased on the day of all M ≥ 7.5 earthquakes with epicenters within 300 km of the mine during the monitoring period and increased after these earthquakes. This is a valuable finding which would give us a clue to understand pre- and post-seismic rockmass behaviors and contribute for progress in earthquake prediction in future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…is is observed because of the persistent variation in the permeability of rock mass, which is due to the variation in strain; this variation is in turn caused by fault movement. Such variations may also occur in an intermediate field (from one to multiple fault lengths) [3]. However, it was shown that those persistent modifications in the groundwater level may even occur in the far field (many fault lengths), up to thousands of kilometers from the epicenter [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…is is observed because of the persistent variation in the permeability of rock mass, which is due to the variation in strain; this variation is in turn caused by fault movement. Such variations may also occur in an intermediate field (from one to multiple fault lengths) [3]. However, it was shown that those persistent modifications in the groundwater level may even occur in the far field (many fault lengths), up to thousands of kilometers from the epicenter [4,5].…”
Section: Introductionmentioning
confidence: 99%